Geology of the canoa formation (pliocene), cliffs of el mangle sector, Montecristi canton, province of Manabi, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2023)
The Canoa formation occurs in El Mangle sector, Montecristi canton, province of Manabí, coastal Ecuador. The outcrops lithologically consist of sandstones, clay sandstones, silty sandstones and silty muddles; it underlies the Tablazo formation and overlies the Angostura formation. In this work, five outcrops were described to determine lithology, essential mineralogical components, deposition, tectonic provenance, biostratigraphy and paleoenvironment; It was achieved as follows, 19 samples for biostratigraphy and lithology, and three thin sections for petrotectonics and petrography. Due to the occurrence of planktonic foraminifera present and extinct in that period, the relative age of the Canoa formation is Pliocene (Zona N18 – N19). The sedimentary paleoenvironment is internal shelf due to the abundance of calcareous and agglutinated benthic foraminifera.
Keywords: Agglutinated; Biostratigraphy; Paleoenvironment; Petrography; Overlay; Outcrops